2022
DOI: 10.1186/s12935-021-02423-8
|View full text |Cite
|
Sign up to set email alerts
|

The B7H4-PDL1 classifier stratifies immuno-phenotype in cervical cancer

Abstract: Background It has been revealed that B7H4 is negatively correlated with PDL1 and identifies immuno-cold tumors in glioma. However, the application of the B7H4-PDL1 classifier in cancers has not been well testified. Methods A pan-cancer analysis was conducted to evaluate the immunological role of B7H4 using the RNA-sequencing data downloaded from the Cancer Genome Atlas (TCGA). Immunohistochemistry (IHC) and multiplexed quantitative immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…Moreover, the expression of PD-L1 also increased. This seems to contradict our ideal result [27,28] . Currently, monoclonal antibodies that block the interaction between PD-1 and PD-L1 by binding to ligands or receptors have shown signi cant clinical e cacy in patients with a variety of cancers [29,30] .…”
Section: Discussioncontrasting
confidence: 74%
“…Moreover, the expression of PD-L1 also increased. This seems to contradict our ideal result [27,28] . Currently, monoclonal antibodies that block the interaction between PD-1 and PD-L1 by binding to ligands or receptors have shown signi cant clinical e cacy in patients with a variety of cancers [29,30] .…”
Section: Discussioncontrasting
confidence: 74%
“…Increasing numbers of research have uncovered that B7-H4 and B7-H5 were abnormally expressed in a variety of human malignant tumor tissues and correlated with disease prognosis [ 12 , 16 , 17 ]. In this study, it was found that B7-H4 and B7-H5 gene expression levels were down-regulated in keratinocytes cell lines of CSCC, and correlated with tumor staging.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, B7-H4 expression in tumors has minimal overlap with PD-L1 (also known as B7-H1) expression ( 17–19 ), which may reflect functional redundancy in inhibiting antitumor immunity. Consequently, in B7-H4+ tumors where PD-L1 expression is absent or low and PD-(L)1 immune checkpoint inhibitors may not be effective, a B7-H4 targeted agent may be an effective treatment option.…”
Section: Introductionmentioning
confidence: 99%